Professional competencies as a component of professional training of a fitness trainer-teacher in higher education institutions - Kornosenko, Oksana; Khomenko, Pavlo; Taranenko, Iryna; Zhamardiy, Valeriy; Shkola, Olena; Tolchieva, Hanna; Saienko, Volodymyr; Batieieva, Nataliya; Kyzim, Petro (My University, 2021)
The article presents professional competencies as an important component in the professional training of future trainers-teachers of fitness in higher education institutions. The purpose of the work is to substantiate professional competencies in the professional training of future trainers-teachers in fitness in higher education institutions. The effectiveness of the use of professional competencies in professional activities is ensured by a combination of medical-biological, social-humanitarian and psychological knowledge from sports and pedagogical disciplines. The learning process is based on integrative interdisciplinary links, unity and interconnection of sports and professional and pedagogical improvement of physical and mental abilities with the use of modern information and communication technologies, cooperation of teachers and fitness trainers, development of international relations and cooperation. The use of modern educational technologies, special computer programs in combination with traditional forms of professional training provides an opportunity to increase the effectiveness of training. In the case of the use of such training in the formation of professional competencies, almost all students are involved in cognitive activities, constant exchange of knowledge. At the same time, information and communication technologies almost naturally combine methods and means of learning and data processing. In order for graduates to become highly qualified and competent professionals, they need not only to acquire a certain set of knowledge and skills, but also to gain sufficient experience in modern information technology, and most importantly, to acquire the ability to self-development, improving their professional competencies.
Professional competencies as a component of professional training of a fitness trainer-teacher in higher education institutions / Oksana Kornosenko, Pavlo Khomenko, Iryna Taranenko, Valeriy Zhamardiy, Olena Shkola, Hanna Tolchieva, Volodymyr Saienko, Nataliya Batieieva, Petro Kyzim // Journal for Educators, Teachers and Trainers, 2021. – Vol. 12(1). – Р. 73 – 81.
Keywords: вищі навчальні заклади, професійні компетенції, тренер-викладач з фітнесу, професійна підготовка; higher education institutions, professional competencies, fitness trainer-teacher, professional training; высшие учебные заведения, профессиональные компетенции, фитнес-тренер-преподаватель, профессиональная подготовка